COMP-15. MOLECULAR AND CLONAL EVOLUTION IN RECURRENT METASTATIC GLIOSARCOMA. (11th November 2019) - Anderson, Kevin; Tan, Aaron; Parkinson, Jonathon; Back, Michael; Kastela, Marina; Newey, Allison; Brewer, Janice; Wheeler, Helen; Hudson, Amanda; Amin, Samirkumar; Johnson, Kevin C; Barthel, Floris; et al.
Abstract: Gliosarcoma, a World Health Organization grade IV glioma, is a rare variant of glioblastoma (GBM) that contains distinct glial and mesenchymal components. Histologically, the glial component matches criteria for glioblastoma, and both components share genetic alterations common to GBM. Though GBM are known to strongly infiltrate surrounding tissue, extracranial metastases are rare, and the underlying mechanisms are still poorly understood. We present a rare case of a 37-year-old woman who was initially diagnosed with IDH wild-type gliosarcoma in the frontal lobe and later developed two local recurrences and extracranial metastases to the vertebral and pelvic bones. In order to understand the clonal relationships between four tumor instances and the origin of metastasis, we performed whole genome sequencing of the intracranial tumors and the tumor located in the right iliac bone. We compared mutational and copy number profiles and inferred tumor clonal phylogeny. The tumors harbored shared GBM alterations including TP53, NF1, and RB1 mutations and CDKN2A deletion. Comparisons of the metastatic to intracranial tumors highlighted a high similarity in molecular profiles, but contrasting evidence regarding the origin of the metastasis. The metastasis was most similar to the second recurrence with respect to mutational signatures, reflected in the activity of signatures associated with defective DNA mismatch repair not observed in the primary or first recurrent tumor. The metastasis was most similar to the first recurrence with respect to copy number profile; both samples displayed widespread amplifications indicative of whole genome doubling. Results of subclonal reconstruction suggested that the second recurrent and metastatic tumors originated from more than one clone and developed subclone-specific driver mutations. The branching phylogeny and copy number profiles suggest the metastasis was largely derived from the first recurrence. This is the first analysis of clonal evolution of extracranial metastasis in gliosarcoma and highlights alterations driving aggressive GBM progression.